THE ALTRUISTIC SIDE OF ARTHUR FLECK AS THE MAIN CHARACTER IN TODD PHILLIPS’ JOKER (2019) - Shita Dewi Ratih Permatasari (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
As a movie character Arthur Fleck, also known as Joker, is represented as a supervillain as well as the archenemy of Batman. He is depicted as a cruel murderer, with a clown-like appearance suffering from mental-illness, who spread the fear and terror in the Gotham city. Using descriptive analysis, characterization and Stephen G. Post’s Altruism and Altruistic Love theory by focusing on Fleck as the main character in this film, this paper is trying to see how he develops his characteristics and reveals his altruistic side. Based on the analysis it is revealed that Fleck has a dynamic character. Even though he is represented as a heartless murderer, his altruistic side is specifically disclosed in some certain aspects